Perioperative Therapy of Oesophagogastric Adenocarcinoma: Mainstay and Future Directions - Katrin Bose; Caspar Franck; Meike N. Müller; Ali Canbay; Alexander Link; Marino Venerito (Gastroenterology Research and Practice)
Perioperative chemotherapy improves overall survival in patients with oesophagogastric adenocarcinoma (OAC) and locoregional disease. The mainstay of perioperative chemotherapy in these patients is a platinum/fluoropyrimidine combination. The phase III FLOT4 trial has shown that the FLOT triplet regimen (oxaliplatin, infusional 5-FU, and docetaxel) improves the outcome of patients with OAC and locoregional disease as compared to the ECF triplet (epirubicin, cisplatin, and infusional 5-FU). Targeted therapies have currently no role in the perioperative setting for the treatment of patients with OAC. For patients with oligometastatic disease, upfront gastrectomy followed by chemotherapy did not show any survival benefit compared with chemotherapy alone and thus should be discouraged. Whether surgery should be offered to patients with metastatic OAC achieving a systemic control after upfront chemotherapy is under scrutiny in the phase III FLOT5/Renaissance trial. After neoadjuvant treatment, lymph node status but not pathologic tumor response is an independent factor in the prediction of overall survival. Growing evidence suggests that perioperative chemotherapy may be associated with an increased mortality risk in patients with microsatellite instable (MSI)/mismatch repair-deficient (MMRD) adenocarcinoma, thus validating poor responsiveness to chemotherapy in MSI patients with locoregional disease.